The Effect of Hydroalcoholic Castor Bean Extract on Spermatogenesis in Mice - R Mohammadi Meyabadi; M Heydari Nasrabadi; P Khodarahmi; S.F Siadat (Institue of Medicinal Plants, ACECR, 2014)
Background: Castor is a plant with various advantages that, it,s anti-fertility effects are seen in some studies. Objective: The aim of this study was to investigate the effect of castor bean extract on spermatogenesis and sperm damage. Methods: 35 male mice were divided into four experimental groups and one control group. Control group received normal saline and experimental groups, received 25, 30, 35 and 45mg/kg body weight Castor bean extract for 30 days respectively. Ten days after the last injection mice were anesthetized and the epididymis and testis were removed. Heart blood samples were collected from mice to measure hormones. After preparing cross-sections of testis, samples were stained and line of cells were counted. The data were analyzed by One - Way ANOVA and Tukey test. Results: Right testicular and epididymal weight and number of spermatogonia, primary spermatocytes, Leydig and Spermatozoa in all experimental groups as well as the diameter in the three groups of 2, 3 and 4 groups were significantly smaller than control group (p<0.05). In experimental group 4, the rate of denaturation of DNA was significantly higher than control group. The Serum sex hormones and percentage of live sperm in the experimental groups 3 and 4, compared to the control group was decreased. Conclusion: Castor bean extract significantly decreases the number of sperm cell lines and sex hormone levels. Furthermore, in higher doses of extract, the sperm DNA denaturation increases. Thus, Castor bean extract may effect on fertility by reducing it.